Improving the cost estimation of space systems : past lessons and future recommendations - Younossi, Obaid; Lorell, Mark A., 1947-; Brancato, Kevin; Cook, Cynthia R., 1965-; Eisman, Mel, 1949-; Fox, Bernard, 1951-; Graser, John C.; Kim, Yool.; Leonard, Robert S.; Pfleeger, Shari Lawrence; Sollinger, Jerry M.; Rand eBooks (Santa Monica, CA : RAND, 2008)
Why have the costs of acquiring space systems been so high? What are the sources of the problems? To answer these questions, RAND researchers examined the sources of cost growth of Air Force space systems and undertook an extensive study of two space systems--the Space Based Infrared System-High (SBIRS) and the Global Positioning System (GPS)--including an evaluation of their sources of cost growth, an assessment of their approaches to technical risk assessment, and an examination of their acquisition policy adaptations and industrial base environments. The researchers recommend independent program assessment for space systems that emphasizes technical and program factors, and a modified organizational structure that maintains cost analyst independence. They also summarize the cost estimating best practices of several other government organizations.
Introduction -- Analysis of the magnitude and sources of cost growth in the SBIRS-High and GPS program -- Technical risk assessment relating to cost estimation for SBIRS-High and GPS -- Other nontechnical SBIRS-High and GPS contributing factors -- SMC organization and cost analysis workforce assessment -- Organizational structure and organizational issues -- Conclusions and recommendations -- Appendix A: AND questionnaire used in interviews with all SMC major program offices, January 2006 -- Appendix B: Findings from other interviews -- Appendix C: Summary of programs currently managed at SMC Appendix D: Details of the SMC cost analyst workload model -- Appendix E: Space systems cost-estimating tools, methods, and data assessment.
"RAND Project Air Force."
"This research was conducted within the Resource Management Program of RAND Project Air Force:--Pref.
Includes bibliographical references (p. 203-211).
Also available on the internet via WWW in PDF format.
Keywords: United States. -- Air Force -- Procurement; Global Positioning System -- Costs; Space surveillance -- United States -- Costs; Electronic books